2008
DOI: 10.1111/j.1939-165x.2008.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ADVIA 120 for analysis of canine cerebrospinal fluid

Abstract: Manual and automated CSF assays had moderate to excellent correlation for WBC and RBC concentrations, but results were more variable for differential cell percentages. The ADVIA assay may be more useful for assessment of canine CSF with adjustment of cell differentiation algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 8 publications
1
33
2
Order By: Relevance
“…, Ruotsalo et al . ) assessed the performance of another automated haematology analyser which had previously been evaluated for CSF analysis in humans (Aune et al . , Danise et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Ruotsalo et al . ) assessed the performance of another automated haematology analyser which had previously been evaluated for CSF analysis in humans (Aune et al . , Danise et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Ruotsalo et al . ). This reflects the need for rapid, precise and, ideally, in‐house techniques with a rapid turn‐around time.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cell counts for erythrocytes are performed similarly. A study conducted to evaluate the usefulness of an automated cell counter in counting and differentiating cell types from canine CSF (Ruotsala et al, 2008) determined moderate correlation between this method and a hemocytometer for leukocyte values and excellent correlation for erythrocytes; however, cell differentials were much more variable. Results from this study also suggested that lymphocytes may be underestimated by manual microscopy in favor of large mononuclears.…”
Section: Cell Countsmentioning
confidence: 98%
“…A study conducted to evaluate the usefulness of an automated cell counter in counting and differentiating cell types from canine CSF (Ruotsala et al, 2008) determined moderate correlation between this method and a hemocytometer for leukocyte values and excellent correlation for erythrocytes; however, cell differentials were much more variable. Cell counts for erythrocytes are performed similarly.…”
Section: Quantitative Analysismentioning
confidence: 99%